THE EFFECET OF STRESS AND PRODUCTIVITY DUE TO TRAFFIC CONGESTION AMONG WORKERS IN KUALA LUMPUR - Syafiq D.R, IIyas; Buqhari, Ahmas; Andy, Onery (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Stress at work’ is a concept which there are lots of potential causes of stress in a working environment that can affect the productivity of a worker. Traffic congestion is a condition in transport that is characterised by slower speeds, longer trip times, and increased vehicular queueing. The experience of workers during traffic congestion before attending work could induce stress towards them, hence being assessed in this study. This study aims to assess the relationship between traffic congestion and work productivity. This study was conducted among a total sample of 133 individual workers in Kuala Lumpur which are prone to road traffic congestion in city areas. Raw data were collected in an online standardized survey. Data analysis was done using Microsoft Excel and SPSS using multiple hypotheses testing formula including ANOVA test, Linear Regression Analysis and Correlation Analysis. The findings of this study concluded that the data from all of the tests show consistent results which there is significant relationship between Stress at Work (p-value <0.05) and Road Traffic Congestion (p-value <0.05), but Work Productivity (p-value >0.05) shows insignificance towards the two variables. Therefore, it can be concluded that road traffic congestion causes stress to workers in Kuala Lumpur, but the stress induced from road traffic congestion does not hinder their productivity at work.